A Contemporary Study Of Supply Chain Management Practice: Issues And Challenges Of Supply Chain Collaboration - Ang, Kok Ching (2005)
The main motivation underlying the SCM is to achieve cost effective and efficient across the entire value chain from logistics management to the inventory management. Besides that, it is aim to achieve higher customer satisfaction level and to remain competitive in the globally fierce competition market.